2000
DOI: 10.1161/01.atv.20.9.2140
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome, LDL Particle Size, and Atherosclerosis

Abstract: Abstract-An operative definition of the metabolic syndrome has been suggested by a working group associated with the World Health Organization in 1998. The aim of this study was to examine whether small, low density lipoprotein (LDL) particle size was associated with the metabolic syndrome and with subclinical atherosclerosis as measured by ultrasound in the carotid and femoral arteries. The study was performed in a population-based sample of clinically healthy men (Nϭ391), all 58 years old and not undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(87 citation statements)
references
References 53 publications
4
81
1
1
Order By: Relevance
“…Small LDL particles have been suggested to be inherently more atherogenic because of their more facile penetration in the arterial wall (22,23) and a greater susceptibility to oxidative modification (24) than large LDL particles. In patients with metabolic syndrome, small LDL particle size was associated with increased intimamedia area in the carotid and femoral arteries (25). In our study, fenofibratetreated subjects had large reductions in small LDL particles (AUC Ϫ495 nmol/l) and smaller increases in large LDL particles relative to placebo-administered subjects (AUC ϩ185 nmol/l) such that total LDL particles were lowered by 19% (P ϭ 0.0033).…”
Section: Safety Studiessupporting
confidence: 46%
“…Small LDL particles have been suggested to be inherently more atherogenic because of their more facile penetration in the arterial wall (22,23) and a greater susceptibility to oxidative modification (24) than large LDL particles. In patients with metabolic syndrome, small LDL particle size was associated with increased intimamedia area in the carotid and femoral arteries (25). In our study, fenofibratetreated subjects had large reductions in small LDL particles (AUC Ϫ495 nmol/l) and smaller increases in large LDL particles relative to placebo-administered subjects (AUC ϩ185 nmol/l) such that total LDL particles were lowered by 19% (P ϭ 0.0033).…”
Section: Safety Studiessupporting
confidence: 46%
“…Mori et al (53,56) showed that DHA and not EPA supplementation increased LDL particle size, suggesting that the lipid-regulating effects of DHA are at least as important as those of EPA. Reduced LDL particle size is an important cardiovascular risk factor (57) and correlates with sub-clinical atherosclerosis as measured by intima-media thickening (58) .…”
Section: Effects On Plasma Lipids and Lipoproteinsmentioning
confidence: 99%
“…The primary objective of the Atherosclerosis and Insulin Resistance (AIR) study was to examine the association between insulin sensitivity and ultrasound-assessed atherosclerosis in 58-year-old men of Swedish ancestry [13]. Exclusion criteria were prevalent cardiovascular disease or treatment with cardiovascular drugs (in order to avoid the confounding effect of treatment on study variables), cancer and other severe disease.…”
Section: Study Populationmentioning
confidence: 99%
“…This syndrome is steadily increasing in modern society and is associated with an increased risk of cardiovascular death [11,12]. A specific feature of the metabolic syndrome and insulin resistance is the increased occurrence of small LDL particles [13].…”
Section: Introductionmentioning
confidence: 99%